1. ## Reasoning word problem

Hey everyone could someone please tell me if im on the right path?

knights always tell the truth
Knaves always lie

Two natives C and D approach you but only C speaks

C says: Both of us are knaves
What are C and D

My work---------

suppose C is a knave
C always lies
C and D are not knaves
then C and D are knight

Next q You encounter natives E and F
E says: F is a knave
F says: E is a knave

My work ------
suppose F is a knave
F lies
E is a knight
E tells the truth
therefore F is a knave

suupose E is a knave
E lies
F is a knight
F tells the truth
therefor E is a knave??

Thankl you

2. Originally Posted by Thetheorycase
Hey everyone could someone please tell me if im on the right path?

knights always tell the truth
Knaves always lie

Two natives C and D approach you but only C speaks

C says: Both of us are knaves
What are C and D

My work---------

suppose B is a knave
C always lies
C and D are not knaves
then C and D are knight

Next q You encounter natives E and F
E says: F is a knave
F says: E is a knave

My work ------
suppose F is a knave
F lies
E is a knight
E tells the truth
therefore F is a knave

suupose E is a knave
E lies
F is a knight
F tells the truth
therefor E is a knave??

Thankl you
After some time I can understand what you were thinking, there is a typo where you wrote B instead of C, also you incorrectly negated the statement "we are both knaves" obtaining "we are both knights" whereas the real negation is "at least one of us is a knight".

I recommend making a table

Code:
C D Possible
============
I I N
I A N
A I Y
A A N
I stands for knight, A stands for knave, and the third column is whether it's possible for C to say "we are both knaves". (C,D) = (A,I) is the only possibility.

For the second one you get to the answer but don't seem to know it. Based on what E says, E being a knave implies F is a knight, which is consistent with what F says. And vice versa. But it's much clearer to write in table form.

Code:
E F Possible
============
I I N
I A Y
A I Y
A A N
The two possible solutions are (E,F) = (I,A) and (E,F) = (A,I).

3. Thank you .. Alot clearer